Pengembangan Media Pembelajaran Blended Learning Berbasis TPACK untuk Meningkatkan Kemampuan Hots Anak Usia 5-6 Tahun - Harsanti, Cita Nugraeni; Rasiman, Rasiman; Buchori, Achmad (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
This research aims to determine children's HOTS abilities through TPACK-based balanced learning media for children aged 5-6 at TK Lestari Krengseng. The approach used in this research. The type of research carried out is the development research method or ADDIE (Analysis, design, development, implementation, evaluation. Sugiyono (2015:407) states that research and development methods are methods used to produce certain products, and test effectiveness of the product. To be able to produce a particular product, research is used in the nature of needs analysis and to test the effectiveness of the product so that it can function in the wider community, research is needed to test the effectiveness of the product. The results of this research are 1) Validation results of Blended Learning based learning media TPACK to improve HOTS abilities of early childhood in kindergarten with very valid criteria. 2) The practicality of the TPACK-based Blended Learning media developed can improve early childhood media in kindergartens based on the results of teacher and student response questionnaires, 3) The effectiveness of learning using TPACK-based Blended Learning media can be seen through effectiveness tests with results namely learning media TPACK-based Blended Learning is able to improve HOTS abilities of early childhood in kindergarten, this is shown by the average score of student learning ability assessment of 90. It can be concluded that the effectiveness of TPACK-based Blended Learning media in improving HOTS abilities and interest in learning in early childhood in very good criteria.